2019
DOI: 10.3389/fimmu.2019.01559
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Pulmonary Embolism in Patients With Pemphigus: A Population-Based Large-Scale Longitudinal Study

Abstract: Growing evidence suggests that inflammation may pose an atypical risk factor for pulmonary embolism (PE), as it drives venous thrombosis via several pathways. The increased risk of PE in several autoimmune diseases has lent weight to this concept. However, the relative risk of PE among patients with pemphigus has not yet been established. We aimed to examine the risk of PE in patients with pemphigus. A large-scale population-based longitudinal cohort study was conducted to evaluate the relative risk (RR) of PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…4 In a population-based large-scale study, the overall risk of pulmonary embolism was 2-fold higher in pemphigus vulgaris patients, reaching a 3.55-fold increase during the first year, then decreasing over time. 11 In the same cohort, presence of peripheral arterial disease, systemic corticosteroid therapy, and smoking were independent factors associated with pulmonary embolism risk. 11 Considering other potential risk factors such as immobilization, or comorbidities, these patients may warrant assessment of the risk benefit ratio of thromboprophylaxis.…”
Section: Discussionmentioning
confidence: 89%
“…4 In a population-based large-scale study, the overall risk of pulmonary embolism was 2-fold higher in pemphigus vulgaris patients, reaching a 3.55-fold increase during the first year, then decreasing over time. 11 In the same cohort, presence of peripheral arterial disease, systemic corticosteroid therapy, and smoking were independent factors associated with pulmonary embolism risk. 11 Considering other potential risk factors such as immobilization, or comorbidities, these patients may warrant assessment of the risk benefit ratio of thromboprophylaxis.…”
Section: Discussionmentioning
confidence: 89%
“…Previous studies revealed that patients with active pemphigus and bullous pemphigoid have higher risk of venous thromboembolism, possibly related to increased expression of tissue factor and pro-inflammatory cytokines leading to a prothrombotic state ( 21 , 22 ). An Italian multicenter cohort study demonstrated a 15-fold risk of venous thromboembolism in patients with active BP ( 21 ), whereas a Israeli population-based study showed a 2-fold risk of pulmonary embolism in pemphigus patients, mainly during the first year of the disease ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that patients with active pemphigus and bullous pemphigoid have higher risk of venous thromboembolism, possibly related to increased expression of tissue factor and pro-inflammatory cytokines leading to a prothrombotic state ( 21 , 22 ). An Italian multicenter cohort study demonstrated a 15-fold risk of venous thromboembolism in patients with active BP ( 21 ), whereas a Israeli population-based study showed a 2-fold risk of pulmonary embolism in pemphigus patients, mainly during the first year of the disease ( 22 ). Additional studies are necessary to determine the benefits of thromboprophylaxis in such patients, especially in the context of COVID-19 pandemic, as the SARS-CoV-2 infection may further activate the coagulation cascade and increase the risk of life-threatening thromboembolic events ( 14 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, pemphigus has about 2-fold risk of pulmonary thromboembolism. 10 The risk is proportional to the intensity of the underlying disease, with treatment with corticosteroids contributing to a reduction in risk. The dermatology guidelines (before as well as after COVID-19 pandemic) have not, however, recommended routine prophylactic anticoagulation in AIBDs.…”
mentioning
confidence: 99%
“…Bullous pemphigoid is known to be a prothrombotic state with approximately 15‐fold increased risk of venous thromboembolism in the acute phase, 9 which decreases to 1.5‐fold during the remission phase. At the same time, pemphigus has about 2‐fold risk of pulmonary thromboembolism 10 . The risk is proportional to the intensity of the underlying disease, with treatment with corticosteroids contributing to a reduction in risk.…”
mentioning
confidence: 99%